1991
DOI: 10.1080/03079459108418756
|View full text |Cite
|
Sign up to set email alerts
|

Chicken anaemia agent: A review

Abstract: Chicken anaemia agent (CAA) is a small, unclassified, icosahedral DNA virus with a single-stranded, circular genome. It seems to have a worldwide distribution. Only one serotype of CAA has been found, and all isolates investigated so far are pathogenic for young chicks. CAA causes a syndrome in chickens characterised by increased mortality, anaemia associated with atrophy of the haematopoietic tissues in the bone marrow, subcutaneous and intramuscular haemorrhages, and atrophy of the lymphoid system. CAA sprea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(108 citation statements)
references
References 54 publications
6
101
0
1
Order By: Relevance
“…All CAV isolates belong to one serotype (McNulty, 1991;Yuasa & Imai, 1986) and the amino acid composition of VP1 is considered to be highly conserved, although Renshaw et al (1996) reported a hypervariable region within VP1 (aa [139][140][141][142][143][144][145][146][147][148][149][150][151] and that amino acid changes within this region influenced the rate of virus replication in cell cultures.…”
Section: Cav Is a Non-enveloped Virus And Is Classified In The Genusmentioning
confidence: 99%
“…All CAV isolates belong to one serotype (McNulty, 1991;Yuasa & Imai, 1986) and the amino acid composition of VP1 is considered to be highly conserved, although Renshaw et al (1996) reported a hypervariable region within VP1 (aa [139][140][141][142][143][144][145][146][147][148][149][150][151] and that amino acid changes within this region influenced the rate of virus replication in cell cultures.…”
Section: Cav Is a Non-enveloped Virus And Is Classified In The Genusmentioning
confidence: 99%
“…Chicken anaemia virus infection is also present in chickens in New Zealand and causes increased mortality, anaemia and atrophy of the lymphoid system, which is likely to predispose affected birds to secondary bacterial, viral and fungal infections (Stanislawek & Howell, 1994). Affected birds may have focal skin lesions characterized by discoloration, skin breakages and exudation (McNulty, 1991), but unlike PBFD, feather and beak abnormalities are not a feature. Circovirus infection in pigeons is associated with a range of lymphoid changes including lymphocellular necrosis, lymphoid depletion and lymphofollicular hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…There are recent reports of small intransigent viruses, which are difficult or impossible to culture other than in the chick embryo. Avian examples of such viruses include the chick anaemia virus, (McNulty, 1991), enteroviruses (including avian encephalomyelitis virus), viruses associated with infectious stunting, astrovirus (duck hepatitis type II), nephritis, English and Belgian enterovirus-like viruses (McNulty, et al, 1990). Frazier et al (1990), reported the detection of three embryo-lethal agents from broiler chickens.…”
Section: Discussionmentioning
confidence: 99%